PENGARUH MODEL ADVANCE ORGANIZER TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA SMP - Anggraini, Novi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract- This research aims to know the influence model of Advance Organizer against the ability of understanding the mathematical concepts of JUNIOR HIGH SCHOOL students in the country 13 Palembang. The methods used in this research is a method of experimentation Posttest Only Control Design. This research population i.e. the whole grade VII in SMP Negeri 13 Palembang. The research in this study samples taken with the technique of Simple Random Sampling, the selected classes, namely Class VII 10 as class experiments amounted to 34 students and Class VII 8 amounted to 32 as the class of the control. Data collection techniques are categorized using the test. Technique of data analysis using t-test. As for the results of the research there were significant effects model Advance Organizer against the ability of understanding the mathematical concepts of grade VII in the SMP Negeri 13 Palembang. Keywords: Model Advance Organizer, the ability of understanding the mathematical concepts. Abstrak- Penelitian ini bertujuan untuk mengetahui pengaruh model Advance Organizer terhadap kemampuan pemahaman konsep matematis siswa SMP. Metode yang digunakan dalam penelitian ini adalah metode eksperimen Posttest Only Control Design. Populasi penelitian ini yaitu seluruh siswa kelas VII di SMP Negeri 13 Palembang. Sampel penelitian dalam penelitian ini diambil dengan teknik Simple Random Sampling, kelas yang terpilih yaitu kelas VII 10 sebagai kelas eksperimen berjumlah 34 siswa dan kelas VII 8 berjumlah 32 sebagai kelas kontrol. Teknik pengumpulan data menggunakan Tes dan LKS. Teknik analisis data menggunakan uji-t. Adapun hasil dari penelitian ini adalah model Advance Organizer terhadap kemampuan pemahaman konsep matematis siswa kelas VII SMP Negeri 13 Palembang. Kata Kunci : Model Advance Organizer, kemampuan pemahaman konsep matematis.